2019
DOI: 10.1111/rssb.12340
|View full text |Cite
|
Sign up to set email alerts
|

The Conditional Permutation Test for Independence While Controlling for Confounders

Abstract: Summary   We propose a general new method, the conditional permutation test, for testing the conditional independence of variables X and Y given a potentially high dimensional random vector Z that may contain confounding factors. The test permutes entries of X non‐uniformly, to respect the existing dependence between X and Z and thus to account for the presence of these confounders. Like the conditional randomization test of Candès and co‐workers in 2018, our test relies on the availability of an approximation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 29 publications
1
81
0
Order By: Relevance
“…Constructing nontrivial knockoffs is a considerable challenge. Numerous methods have been proposed, including but not limited to: second-order Gaussian knockoffs (Candès et al, 2018); conditional permutation sampling (Berrett et al, 2020); hidden Markov models (Sesia et al, 2019); generative deep neural networks (Romano et al, 2020); Metropolis-Hastings sampling (Bates et al, 2020); conditional density estimation (Tansey et al, 2021); and normalizing flows (Hansen et al, 2021). A complete review of these proposals is beyond the scope of this chapter.…”
Section: The Knockoff Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing nontrivial knockoffs is a considerable challenge. Numerous methods have been proposed, including but not limited to: second-order Gaussian knockoffs (Candès et al, 2018); conditional permutation sampling (Berrett et al, 2020); hidden Markov models (Sesia et al, 2019); generative deep neural networks (Romano et al, 2020); Metropolis-Hastings sampling (Bates et al, 2020); conditional density estimation (Tansey et al, 2021); and normalizing flows (Hansen et al, 2021). A complete review of these proposals is beyond the scope of this chapter.…”
Section: The Knockoff Frameworkmentioning
confidence: 99%
“…Experiments indicate that the CRT is slightly more powerful than the ATT, but the authors caution that the former is computationally intensive and do not recommend it for large datasets. That has not stopped other groups from advancing formally similar proposals (e.g., Berrett et al, 2020;Tansey et al, 2021).…”
Section: The Knockoff Frameworkmentioning
confidence: 99%
“…However, subsequent studies showed that this procedure was less efficient than regular PC correction for dealing with fine-scale population structure 21 . Recently, a general new method, the conditional permutation test , for testing the conditional independence of variables X and Y given a potentially high dimensional random vector Z that may contain confounding factors was proposed 42 . The test permutes entries of X non-uniformly, to respect the existing dependence between X and Z and thus to account for the presence of these confounders.…”
Section: Methodsmentioning
confidence: 99%
“…The test permutes entries of X non-uniformly, to respect the existing dependence between X and Z and thus to account for the presence of these confounders. However, like the conditional randomization test of Candès et al 43 , the test relies on the availability of an approximation to the distribution of X/Z and sensitivity analysis to the misspecification of the distribution parameters showed that the method suffered from a type I error inflation increasing with the misspecification level 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Only limited extensions for non-Gaussian variables [15,31] and for nonlinear dependences [16,30] exist. Other approaches include combining a series of unconditional independence tests on the response variables (X, Y ) conditional on multiple individual values z of Z [25,17]; tests based on measures of statistical distance between estimates of the conditional densities p X|Z and p X|Y Z , which are zero if and only if X ⊥ ⊥ Y | Z [37,38]; tests based on 156 ONUR TEYMUR AND SARAH FILIPPI estimation of the conditional mutual information of X and Y given Z [19,32,33]; permutation-type tests [4,3] that require knowledge of or estimation of p X|Z ; and a large range of kernel-based methods [9,41,5,40,36] typically designed with the aim of dealing with high-dimensional or sparse problems more effectively.…”
mentioning
confidence: 99%